Evaluation of HER and OER electrocatalytic activity over RuO2–Fe2O3 nanocomposite deposited on HrGO nanosheets. (15th January 2023) - Mosallaei, Hamta; Hadadzadeh, Hassan; Ensafi, Ali A.; Mousaabadi, Kimia Zarean; Weil, Matthias; Foelske, Annette; Sauer, Markus
Abstract: Electrochemical water-splitting efficiency is determined by both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) electrocatalysts. Therefore, designing a bi-functional configuration is essential for an efficient HER and OER catalytic performance under the same experimental conditions. In this study, a novel ionic pentanuclear complex of the type [Ru(dmbpy)3 ]3 [Fe(CN)6 ]2, where dmbpy = 4, 4′-dimethyl-2, 2′-bipyridine, has been synthesized and characterized by structural (X-ray), analytical (CHN), and spectral (FT–IR, UV–Vis) methods. Highly reduced graphene oxide nanosheets (HrGO NSs) supported RuO2 –Fe2 O3 nanocomposite were prepared by an impregnation method using [Ru(dmbpy)3 ]3 [Fe(CN)6 ]2 as a precursor and HrGO NSs as a support. The RuO2 –Fe2 O3 /HrGO NSs nanocomposite was characterized by means of spectroscopy (XPS, FT–IR, and FT–Raman), surface area (BET/BJH), diffraction (XRD), thermal (TGA), and electron microscopy (TEM and FE–SEM) analyses. The electrocatalytic HER, OER, and overall water-splitting activities of RuO2 –Fe2 O3 /HrGO NSs, RuO2 –Fe2 O3, RuO2 /HrGO, Fe2 O3 /HrGO, and HrGO in 1 M KOH solution were studied. According to the overpotentials of −239 and 386 mV ( vs . RHE) at 10 mA cm −2 current density, the exchange current densities of 0.0641 and 0.389 × 10 −4  mA cm −2, the Tafel slopes of 97 and 67 mV dec −1, and the charge-transfer resistance values of 38.57 and 31.5 Ω for HER and OER, respectively, the RuO2 –Fe2 O3 /HrGO NSs nanocomposite possesses bi-functional catalytic capabilities toward both hydrogen and oxygen evolution reactions. The catalytic performance is enhanced by the high surface area, the high number of catalytically active sites, the presence of nanoparticles with different morphologies, and the synergistic interaction between RuO2 –Fe2 O3 nanoparticles and HrGO nanosheets. Graphical abstract: Image 1 Highlights: Designing a bi-functional configuration for an efficient HER and OER catalytic performance. Synthesis of a novel ionic pentanuclear precursor of the type [Ru(dmbpy)3 ]3 [Fe(CN)6 ]2 . Preparation of highly reduced graphene oxide nanosheets supported RuO2 –Fe2 O3 nanocomposite. Synergistic interaction between RuO2 –Fe2 O3 and HrGO to enhance the electrocatalytic performance.